(untitled) (International Seven Journal of Multidisciplinary, 2023)
Securing funding through calls for proposals is a crucial strategy for organizations seeking to implement social projects. This article examines the process of obtaining resources via public and private calls, emphasizing the importance of aligning project objectives with donor priorities and adhering to rigorous project management practices. Effective project design, transparent financial planning, and robust monitoring and evaluation mechanisms are essential for enhancing the likelihood of success in securing and managing grant-funded projects.